2017
DOI: 10.3892/etm.2017.4607
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in biomechanical properties and microstructure of colon wall in early-stage experimental colitis

Abstract: The aim of the current study was to investigate the effects of early-stage dextran sodium sulfate (DSS)-induced mouse colitis on the biomechanical properties and microstructure of colon walls. In the present study, colitis was induced in 8-week-old mice by the oral administration of DSS, and then 10 control and 10 experimental colitis samples were harvested. Uniaxial tensile tests were performed to measure the ultimate tensile strength and ultimate stretches of colon tissues. In addition, histological investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Severe alterations of the cell membrane and nucleus were also observed. The changes observed among smooth muscle cells and collagen fibers indicated that the colon wall in UC was less resistant to external forces, as previously reported by the authors of the current study ( 32 ). Changes in the morphology of these cells may indicate epithelial cell injury.…”
Section: Discussionsupporting
confidence: 89%
“…Severe alterations of the cell membrane and nucleus were also observed. The changes observed among smooth muscle cells and collagen fibers indicated that the colon wall in UC was less resistant to external forces, as previously reported by the authors of the current study ( 32 ). Changes in the morphology of these cells may indicate epithelial cell injury.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, most studies did not consider this through-thickness heterogeneity when characterizing the macroscopic biomechanics of the colon and rectum. An array of conventional mechanical testing methods have been applied to characterize the macroscopic mechanical features of the large intestine, including uniaxial tensile stretch [ 16 , 17 , 18 ], biaxial tensile stretch [ 19 , 20 , 21 ], planar compression [ 22 , 23 ], indentation [ 24 , 25 ], shear [ 22 ], and luminal inflation [ 26 , 27 , 28 , 29 ]. Overall, the mechanical response of the large intestine is governed by the geometrical (large strains in vivo) and material nonlinearities of the tissue with its embedded bundles of collagen and muscle fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Although billions of dollars are spent annually to treat GI disorders and a great number of clinical and statistical success studies have been reported, and comparatively very few engineers are working in the GI research [1]. The favored research directions include pharmaceutical drug testing [2][3][4][5][6][7][8][9] and a virgin passive, fiber-enhanced anisotropic mechanical characterization of the intestine [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Other mechanical aspects such as smooth muscle contraction, stress-softening and viscoelasticity have yet to be investigated with further detail.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanical aspects such as smooth muscle contraction, stress-softening and viscoelasticity have yet to be investigated with further detail. Furthermore, isotropic material [25][26][27][28][29][30][31] and anisotropic [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] material modelings of the intestine specimen from uniaxial and inflation-biaxial have been widely studied so far within the range of a virgin-passive deformation state. Throughout this paper, the term 'passive' refers to the non-contractile component of the material's stiffness and 'virgin' refers to a state of stress-strain response without stress-softening or stiffness reduction due to material damage [32][33][34].…”
Section: Introductionmentioning
confidence: 99%